The examination of detrusor underactivity in multiple system atrophy - Yamamoto, Tatsuya; Sakakibara, Ryuji; Uchiyama, Tomoyuki; Kuwabara, Satoshi (Frontiers in Neurology, 2024)
Aims The urinary dysfunction in multiple system atrophy (MSA) is characterized by large post-void residuals (PVR) due to impaired bladder contractility. However, the evaluations of bladder contractility are not well validated in MSA. Because the bladder contractility index can be generally represented as Pdet Qmax (detrusor pressure at maximum urinary flow rate) + kQmax (maximum urinary flow rate), we aim to examine which “k” value is suitable for representing bladder contractility concerning its correlations to PVR and voided percentage (VOID%). Methods We retrospectively reviewed 133 patients with MSA (74 males, 59 females, mean disease duration 3.2 years) who underwent an urodynamic study. We calculated bladder contractility using the formula PIPk = Pdet Qmax + kQmax by increasing the “k” value from 0.1 to 10 by increments of 0.1. We calculated the correlations between each PIPk (k = 0.1–10.0) and PVR and VOID%. Results The correlational coefficients between PIPk and VOID% were larger than those between PIPk and PVR. The correlational coefficients between PIPk and VOID% reached a plateau level at a “k” value >5.0 in male patients, suggesting that currently used formulas such as Pdet Qmax + 5Qmax for males might be appropriate for male MSA patients. However, the correlational coefficients between PIPk and VOID% reached a plateau level in female patients when the “k” values were >6.0, which might overestimate bladder contractility in female patients. Conclusion Although currently used formulas such as Pdet Qmax + 5Qmax might be appropriate for male MSA patients, formulas for female patients need further evaluation.